Design and Development of an Electrical Power Prediction of a Small-Scale Hydrokinetic Turbine (Borneo Engineering & Advanced Multidisciplinary International Journal, 2025)
Hydrokinetic turbine (HKT) technology harnesses kinetic energy from rivers with low slopes. Turbem software is frequently used to simulate and estimate the output power of HKT systems; however, its predictions often overestimate actual performance. To achieve more accurate estimates, a combination of Blade Element Momentum (BEM) theory and experimentation is recommended. In this study, a small-scale HKT system with a turbine diameter of 0.3 meters and a fixed blade angle of 13° was analyzed. BEM theory was employed to estimate the power coefficient (Cp) and the tangential-to-water flow velocity ratio (λ), yielding a Cp value of 0.25 and a tip-speed ratio (TSR) of approximately 5. Based on these parameters, the optimal output power of a Direct Current (DC) Permanent Magnet Generator was determined to correspond to rotational speeds ranging from 196 to 343 rpm, considering a gear ratio of 1.75 and a transmission efficiency of 88%. The relationship between the generator's power output and its rotational speed was experimentally validated under full-load conditions, using 12 V DC LED bulbs as load resistors. The results demonstrated a strong correlation, with a R2 value of 0.9965. A predicted power output versus rotational speed graph was generated and compared with field data. The results revealed prediction errors of 16% for power output and 5% for rotational speed, which were deemed acceptable for river velocities between 0.8 and 1.4 m/s.